2020
DOI: 10.3390/ijerph18010152
|View full text |Cite
|
Sign up to set email alerts
|

Parental Stress, Anxiety and Depression Symptoms Associated with Self-Efficacy in Paediatric Type 1 Diabetes: A Literature Review

Abstract: Background: Parents play a significant role in the management and monitoring of their children’s Type 1 diabetes mellitus (T1DM), being considered a family disease. The current review intends to investigate parental stress, depression and anxiety symptoms associated with self-efficacy referred to paediatric diabetes management. Method: A literature review was carried out using PsycINFO, Web of Science and PubMed where the following terms were considered: diabetes mellitus, paediatric, parent-child relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 53 publications
(136 reference statements)
3
47
0
4
Order By: Relevance
“…Partially in line with our hypotheses, parents of children with chronic diseases reported significantly more anxiety, but not more depressive symptoms, compared to parents of healthy children. These findings are in line with other studies reporting high anxiety scores in parents of children with chronic diseases (e.g., Bassi et al, 2020 ; Jones & Reilly, 2016 ; Kelada et al, 2020 ). However, literature on the topic of parental well-being of children with chronic diseases is not univocal (e.g., Kelada et al, 2020 ; Ljungman et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Partially in line with our hypotheses, parents of children with chronic diseases reported significantly more anxiety, but not more depressive symptoms, compared to parents of healthy children. These findings are in line with other studies reporting high anxiety scores in parents of children with chronic diseases (e.g., Bassi et al, 2020 ; Jones & Reilly, 2016 ; Kelada et al, 2020 ). However, literature on the topic of parental well-being of children with chronic diseases is not univocal (e.g., Kelada et al, 2020 ; Ljungman et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…Parents of children suffering from chronic diseases are generally particularly vulnerable for experiencing psychological distress (i.e., depressive symptoms and anxiety) and parenting distress (e.g., Bassi et al, 2020 ; Jones & Reilly, 2016 ; Kelada et al, 2020 ; Ljungman et al, 2014 ). These parents also report lower overall parental quality of life than parents of healthy children ( Goldbeck, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common disabling mental illness. Human susceptibility to depression has changed with variations in lifestyles, such as diet and sleep, and increased social stress (Bassi et al, 2020;Marx et al, 2021;Sweetman et al, 2021). Affluent environments will reduce depressive manifestations, while the majority of depressed patients in low-and middle-income countries do not receive effective treatment (Evans-Lacko et al, 2018;Gu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review, 19% of parents experienced psychological distress lasting 1–4 years after their children were diagnosed with Type 1 diabetes ( 10 ). Bassi ( 11 ) reported that the prevalence of depression among the parents of adolescents with Type 1 diabetes ranged from 13 to 74% in different studies. Evidence from empirical research suggests that parental depressive symptoms and diabetes distress are negatively associated with pediatric glycaemic control ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%